Challenges in Implementing Online Administrative Services for Civil Registration: A Case Study of Plavon Website - Oktavia, Elvira Nur; Choiriyah , Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to evaluate the effectiveness of the Plavon website, an online service introduced by the Civil Registry Office in Sidoarjo, Indonesia, for population administration. The innovative service, initiated in 2021, aimed to streamline document processing for citizens, including birth certificates, change of address notices, family cards, identity cards, and death certificates. Utilizing a descriptive qualitative research method and employing data collection techniques such as observation, interviews, and documentation, this study employed both primary and secondary data. The research utilized purposive sampling and focused on e-government effectiveness theory. The findings indicate that the Plavon website has not reached its intended audience effectively. Many elderly individuals lack understanding of its usage, possess no smartphones, or face technological gaps with smartphones and computers. Suboptimal program awareness among the populace remains a challenge. Additionally, the program lacks clear operational instructions, particularly regarding the implementation of the Plavon website. Despite operating under the legal framework of Ministerial Regulation No. 7 of 2019 for online population administration services, this study highlights crucial gaps in implementation and audience outreach, indicating the need for strategic improvements and enhanced public awareness campaigns. Highlights: Accessibility Gap: Elderly and Technologically Disadvantaged: Elderly individuals and those lacking technological proficiency face challenges accessing and utilizing the Plavon website for administrative services. Program Awareness Deficiency: Limited Understanding and Outreach: The study reveals insufficient public awareness about the Plavon website, indicating a need for enhanced educational campaigns and outreach strategies. Implementation and Instructional Shortcomings: Lack of Clear Operational Guidelines: Deficiencies in providing clear operational instructions for using the Plavon website hinder its effective implementation, demanding improved procedural guidance for users. Keywords: Online Civil Registration, E-Government, Plavon Website, Administrative Services, Public Awareness